Respuesta :

Answer:

x = -1

y = -5

Step-by-step explanation:

y = x - 4                                     y = x - 4

2x + 3y = -17                             y = (-1) - 4

2x + 3(x - 4) = -17                      y = -1 - 4

2x + 3x - 12 = -17                       y = -5

5x - 12 = -17

5x - 12 + 12 = -17 + 12                 Check

5x = -5                                    2x + 3y = -17

5x/5 = -5/5                           2(-1) + 3(-5) = -17

x = -1                                        -2 + -15 = -17

                                                   -17 = -17

what they said up there ^^